Pro ADO.NET Data Services: Working with RESTful Data - Shaw, John (Apress, 2012)
Paradoxically, ADO.NET Data Services is big on concepts and fuses together many technologies in the Microsoft stack. Therefore, let us not confuse elegance with simplicity; developing a data service is a hugely productive yet deceptively complex undertaking that requires no less consideration than developing any other kind of service.«$